2007
DOI: 10.5194/acp-7-4943-2007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of gravity waves into the atmosphere during the March 2006 total solar eclipse

Abstract: Abstract. This study aims at providing experimental evidence, to support the hypothesis according to which the movement of the moon's shadow sweeping the ozone layer at supersonic speed, during a solar eclipse, creates gravity waves in the atmosphere. An experiment was conducted to study eclipse induced thermal fluctuations in the ozone layer (via measurements of total ozone column, ozone photolysis rates and UV irradiance), the ionosphere (Ionosonde Total Electron Content -ITEC, peak electron density height -… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 36 publications
3
33
0
Order By: Relevance
“…Modeling studies supported the idea of eclipse-induced gravity wave generation in the thermosphere (Ridley et al, 1984;Roble et al, 1986;Muller-Wodarg et al, 1998), which is also supported by measurements (Liu et al, 1998;Altadill et al, 2001;Sauli et al, 2006). Zerefos et al (2007) reported waves with periods ranging from 30 to 40 min associated with thermal stratospheric ozone forcing. Singh et al (1989) have reported waves with a period of 10-40 min measured at more than 50 km from the zone of totality.…”
Section: Introductionsupporting
confidence: 69%
“…Modeling studies supported the idea of eclipse-induced gravity wave generation in the thermosphere (Ridley et al, 1984;Roble et al, 1986;Muller-Wodarg et al, 1998), which is also supported by measurements (Liu et al, 1998;Altadill et al, 2001;Sauli et al, 2006). Zerefos et al (2007) reported waves with periods ranging from 30 to 40 min associated with thermal stratospheric ozone forcing. Singh et al (1989) have reported waves with a period of 10-40 min measured at more than 50 km from the zone of totality.…”
Section: Introductionsupporting
confidence: 69%
“…The GWs generated in this region propagate upward as suggested by Chimonas and Hines [1970]. Zerefos et al [2007], for March 2006 total solar eclipse by using different measurement techniques for the troposphere, stratosphere, and ionosphere, showed the presence of GWs in the stratosphere and ionosphere with periods of~30-40 min. Zhang et al [2010], for the 22 July 2009 SE, using ionospheric back scatter sounding data recorded at Wuhan (30.5°N; 114.35°E), China, observed medium scales traveling ionospheric disturbances (MSTIDs) of a 40 min period from ED fluctuations in the Es and F regions.…”
Section: 1002/2013ja019521mentioning
confidence: 76%
“…Apart from wide range of implications of SEs on the near Earth's atmosphere and ionosphere, the two most important consequences of SEs are ionospheric variability due to sudden cutoff of solar radiation for a short duration and generation of gravity waves (GWs) [Chimonas, 1970;Zerefos et al, 2007;Babakhanov et al, 2013]. The passage of solar terminator is another main in situ source of GWs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sudden drop in the incoming solar radiation causes the cooling of the surface and higher up, resulting in the changes of atmospheric temperatures. These temperature variations drive changes in pressures and winds (Ballard et al 1969;Anderson et al 1972;Founda et al 2007;Gerasopoulos et al 2007;Kameda et al 2009;Wang and Liu 2010), and induces vertically propagating gravity waves (e.g., Chimonas 1970;Chimonas and Hines 1971;Seykora et al 1985;Zerefos et al 2007). Solar eclipse also changes the ionosphere total electron density (Le et al 2009).…”
Section: Introductionmentioning
confidence: 99%